Smart ultrasound device for real-time myocardial stiffness quantification of the human heart. (8th February 2021) - Pedreira, O; Papadacci, C; Chatelin, S; Correia, M; Tanter, M; Goudot, G; Messas, E; Pernot, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): ERC Introduction: Myocardial stiffness (MS) is crucial to understand cardiac biomechanics and evaluate cardiac function. We recently demonstrated that shear wave imaging using acoustic radiation force can provide quantitative end-diastolic MS in human patients [1] . However, the dependence of shear wave velocity with myofiber orientation remained a limitation and required to perform Shear Wave Velocity (SWV) estimations from different probe orientations which is challenging in clinical practice. We propose a new approach to provide real-time quantitative assessment of MS without dependence of the probe orientation based on a dedicated smart ultrasound (US) device. Methods: A new US probe was designed and manufactured to generate acoustic radiation force along the central axis and track the SWV simultaneously along three different orientations to obtain an elliptic profile of SWS. The probe was connected to dedicated electronics and software to provide real-time end-diastolic MS with ECG gating. Validation was performed on 4 in-vitro calibrated phantoms (0.92 – 1.49 – 2.58 – 3.49 m/s) and on ex vivo porcine hearts. MS along and across the fibers were compared to the values measured by conventional shear wave imaging with a linear probe mounted on a rotation motor (angular step of 10°) (Aixplorer, Supersonic imaging). Finally, the in vivo feasibility and reproducibility of measuring MS of the antero-septal wall and of the right ventricular (RV) wall was assessed transthoracically on four human volunteer . Results: In vitro results on phantoms showed a good agreement with calibrated value (r2 = 0.98, std = 4.8%). Elliptic profiles on ex-vivo porcine heart showed good agreement with Aixplorer measurements acquired at different angles, with a relative difference along the long axis (LA) of: Δ=7.0%, Δ=7.1%, Δ=9% respectively for left ventricle (LV), right ventricle (RV) and septum. Finally, myocardial SWV assessment in human volunteers was obtained successfully on the RV and on the septum in late diastole. The mean MS was 1.79+/- 0.15 m/s along the fiber direction, the fractional anisotropy (FA) was 0.25 +/- 0.06 on septal wall in good agreement with previous results [1] and 1.06 +/- 0.11 m/s along fibers orientation and a FA of 0.27 +/- 0.08 on RV. Finally the beat to beat reproducibility of MS measurement was estimated to be 8.22%. Conclusion: The new smart US device allowed non-invasive quantification of anisotropic myocardial tissues in real time. Results showed the accuracy of the methods. This approach could offer a new clinical tool for the evaluation of the myocardium in cardiomyopathies and in heart failure patients.